Functional Analysis of the Melanin-Associated Gene CmMR1 in Coniothyrium minitans - Luo, Chenwei; Zhao, Huizhang; Yang, Xiaoxiang; Qiang, Cuicui; Cheng, Jiasen; Xie, Jiatao; Chen, Tao; Jiang, Daohong; Fu, Yanping (Frontiers in Microbiology, 2018)
Coniothyrium minitans is a sclerotial parasite, which has been investigated for commercial control of crop diseases caused by Sclerotinia sclerotiorum. Previously, we obtained a T-DNA insertional mutant, ZS-1TN24363, which did not produce melanin during conidiation. To understand the function of melanin in C. minitans, we cloned the gene that was disrupted by the T-DNA insertion, and found that this gene, called CmMR1, encoded a putative protein of 1,011 amino acids, which is a homolog of the transcription factor MR. Full-length CmMR1 contains 3,167 bp, with three exons and two introns. To confirm that the disrupted gene is responsible for the melanin-deficiency of the mutant, CmMR1 was disrupted and three targeted knockout mutants were obtained. Biological assays showed that the phenotype of the targeted knockout mutants was similar to that of the T-DNA insertional mutant. Furthermore, gene complementation confirmed that CmMR1 is responsible for the mutant phenotype. CmMR1 disruption did not affect hyphal growth, conidiation, and parasitization of C. minitans, however, the ROS accumulation increased and tolerance to UV light decreased significantly in the mutants. Our result may enhance the understanding of melanin in the ecology of C. minitans on molecular level.